Role of early screening for diabetic retinopathy in patients with diabetes mellitus: An overview - Praveen Vashist; Sameeksha Singh; Noopur Gupta; Rohit Saxena (Wolters Kluwer Medknow Publications, 2011)
Diabetes has emerged as a major public health problem in India. It is estimated that there were 40 million persons with diabetes in India in 2007 and this number is predicted to rise to almost 70 million by 2025. The impact of rapid urbanization, industrialization and lifestyle changes has led to an increasing trend in prevalence of diabetes and its associated complications such as neuropathy, nephropathy, vascular diseases (cardiac, cerebral and peripheral) and retinopathy. Diabetic retinopathy is a important cause of avoidable blindness in India. Treatment interventions at early stages of diabetic retinopathy can reduce burden of blindness due to diabetic retinopathy. With the available cost-effective methods of early screening, appropriate strategies/models need to be developed. Such models need to have a well-developed mode for screening, diagnosis and referral at each hierarchal level beginning from primary health centers to specialized institutes for eye care. The National Program for Control of Blindness of India recommends opportunistic screening for identification of diabetic retinopathy. Every opportunity of contact with high-risk cases for diabetes and/or diabetic retinopathy should be utilized for screening, diagnosis and referral. All the stakeholders including the private sector will need to play a role. Along with this, awareness generation and behavior change amongst the diabetics and care support systems should also be part of the overall model. A major role can be played by community participation and improving the health seeking behavior among diabetics in order to reach a larger population and increasing the compliance for continued care.